2021
DOI: 10.1038/s41392-020-00437-8
|View full text |Cite
|
Sign up to set email alerts
|

CREBBP/EP300 mutations promoted tumor progression in diffuse large B-cell lymphoma through altering tumor-associated macrophage polarization via FBXW7-NOTCH-CCL2/CSF1 axis

Abstract: Epigenetic alterations play an important role in tumor progression of diffuse large B-cell lymphoma (DLBCL). However, the biological relevance of epigenetic gene mutations on tumor microenvironment remains to be determined. The core set of genes relating to histone methylation (KMT2D, KMT2C, EZH2), histone acetylation (CREBBP, EP300), DNA methylation (TET2), and chromatin remodeling (ARID1A) were detected in the training cohort of 316 patients by whole-genome/exome sequencing (WGS/WES) and in the validation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 62 publications
5
83
0
Order By: Relevance
“…They were detrimental in cancers such as pheochromocytoma and paraganglioma, kidney chromophobe and uveal melanoma, and protective in diffuse large B-cell lymphoma, prostate adenocarcinoma and thyroid cancer ( Fig. 5 D), which is partly in accordance with previous studies [59] , while not compatible with others [60] , [61] . The protective role of MScore in some cancers indicated the heterogeneity of the tumor microenvironment among different cancer types.…”
Section: Resultssupporting
confidence: 88%
“…They were detrimental in cancers such as pheochromocytoma and paraganglioma, kidney chromophobe and uveal melanoma, and protective in diffuse large B-cell lymphoma, prostate adenocarcinoma and thyroid cancer ( Fig. 5 D), which is partly in accordance with previous studies [59] , while not compatible with others [60] , [61] . The protective role of MScore in some cancers indicated the heterogeneity of the tumor microenvironment among different cancer types.…”
Section: Resultssupporting
confidence: 88%
“…48 In contrast, another recent study found that DLBCL patients with CREBBP/EP300 mutations had significantly poorer survival and decreased peripheral blood lymphocyte to monocyte ratios, and that in DLBCL xenograft murine models, mutations in CREBBP and EP300 activated the NOTCH signaling pathway and promoted macrophage polarization to M2 phenotype. 49 In summary, KMT2D nonsynonymous mutations are associated with DLBCL genomic instability, and genomic complexity is associated with poor prognosis and decreased T cells and PD-L1 expression in macrophages and B cells in DLBCL with wild-type TP53. Further studies elucidating the oncogenic and neoantigen roles of DLBCL mutations in DLBCL patients are needed, as well as the therapeutic implications of genetic and immune biomarkers.…”
Section: Discussionmentioning
confidence: 94%
“… 48 In contrast, another recent study found that DLBCL patients with CREBBP / EP300 mutations had significantly poorer survival and decreased peripheral blood lymphocyte to monocyte ratios, and that in DLBCL xenograft murine models, mutations in CREBBP and EP300 activated the NOTCH signaling pathway and promoted macrophage polarization to M2 phenotype. 49 …”
Section: Discussionmentioning
confidence: 99%
“…CCR2 inhibitors induce the accumulation of monocytes in bone marrow, resulting in reduced numbers of TAMs [ 51 ]. Yao et al reported that CREBBP/EP300 mutations could regulate the FBXW7-NOTCH-CCL2/CSF1, polarizing TAMs to the M2 phenotype and promoting cell proliferation in DLBCL [ 52 ].…”
Section: Introductionmentioning
confidence: 99%